(untitled) (Studia Prawnicze / The Legal Studies, 1985)
The article discuSises the actual, binding in. the FRG since 1976, regulation of abortion by penal law. The first part presents basic stages of German legislation in this respect. It was stated that, originally — under the influence of Roman law — there was an absolute interdiction to terminate a pregnancy, accepted later in the penal code of the Reich of 1871. Attempts to weaken this interdiction were especially strong on the turn of the 19th century. They resulted in the fact that in 1927 the Court of the Reich, for the first time, permitted of abortion in view of the health or life of the pregnant woman. The regulation comprising this situation was later included in the government draft of the new penal code of 1962. The so-called alternative draft was presented, as a counterproposal and it exerted an. especially strong influence on the course of the reform. First of all, it VMS a basis of the law of 1974 which introducted so-called time limit model in relation to abortion. The law was, however, appealed against and recognized by the Federal Constitutional Tribunal ais not in conformity with the Can’stitution. Finally, the so-called model of indication was accepted which has been binding till now. The above mentioned solution was in details discussed in the second part of the article. The model compriSes a basic interdiction to terminate a pregnancy (§ 218 of the penal code). An early stage of a pregnancy is free from intervention by law, and exceptions from the interdiction to terminate a pregnancy have been provided for. In particular, it permits of abortion if there are medical, eugenic, criminological indications and a general critical situation of the pregnant woman, and also when the pregnant woman gives her consent, the abortion is carried out by a doctor who want’s to save her. The code provides for the exclusion of criminal responsibility in relation to the pregnant woman if a pregnancy is terminated by the doctOr up to 22 weeks of it and the woman has seeked guidance on this matter. There is also a possibility to depart from the punishment towards the pregnant woman if she has found herself in. a particulartly difficult situation. The code also inIcludes many additional provisions i.e. on the pregnant woman’s obligation to seek guidance, obligation to carry out an abortion in a hospital or in premises approved for the purpose, and a prohibition to advertise and sell any means which could be used in procuring an abortion. In the third part of the article the author mentions that the fact of coming into force of the new penal code regulation on abortion has not appeased animated discussions and disputes in this field. On the one hand, it is said that the solution inadequatelly protects nascent life, on the other hand, it is said to restrict too much woman’s right to decide about herself